Optimal Dietary Crude Protein in Commercial Feeds for Shrimp and Halophytes in Marine Aquaponic Biofloc Systems - Chu, Yu-Ting; Brown, Paul B. (Frontiers in Marine Science, 2022)
Formulated diets for animals is the primary source of nutrients in aquaponic systems that need to maintain beneficial bacteria as well as for plants. Dietary protein is one of the expensive macronutrients in fish diets, especially when fishmeal is used, and it is the source of nitrogen (N) for other biotic components. Biofloc has the potential to serve as the supplement diet for shrimp and reduce the need of expensive protein. However, it is not clear if low dietary protein will be adequate to support the three organisms (animals, plants, and bacteria) in an aquaponic system operated with biofloc technology. The aim of the present study was to investigate the effect of shrimp feed with different protein concentrations (30%, 35%, or 40%) on water quality and the growth performance of Pacific whiteleg shrimp (Litopenaeus vannamei) and three edible halophytic plants (Atriplex hortensis, Salsola komarovii, and Plantago coronopus) in biofloc-based marine aquaponics. The experiment was conducted for 12 weeks, the plants were harvested and seedlings transplanted every 4 weeks. Dietary protein content did not influence shrimp growth in the current study, indicating that feeds with lower protein concentrations can be used in biofloc-based marine aquaponic systems. During the early and mid-stages of cultivation, plants grew better when supplied diets with higher protein concentration, whereas no differences were observed for later harvests. Hence, for maximum production with mature systems or in the scenario of high concentration of nitrate, providing a higher protein concentration feed in the early stages of system start-up, and switching to a lower protein concentration feed in later stages of cultivation was recommended.